Enhancement of convective heat transfer using magnetically flapping fin array. (December 2021) - Nguyen, Thien-Binh; Liu, Dongdong; Raut, Harshal; Bhattacharya, Amitabh; Sharma, Atul; Tran, Tuan
Abstract: Electronic devices with high power density require efficient and compact heat transfer management methods. While passive fins have been routinely used for heat dissipation, they usually have a limited range of operating conditions in electronic applications. In this study, we explore experimentally and numerically active enhancement of convective heat transfer using a magnetically actuated array of fins. In our experiments, the fins are rectangular nickel strips attached to a silicon substrate via flexible joints and actuated by an alternating electromagnetic field. We observe that angular oscillation of the fins leads to significant enhancement in heat transfer coefficient. Specifically, at high actuation frequencies and amplitudes, the heat flux enhancement for a fixed wall temperature may be up to 100%. We examine the scaling between the measured heat flux, frequency, and temperature difference. For an actively cooled substrate, the Nusselt number is primarily determined by forced convection due to fin motion, while the contribution from buoyancy is weak. In our two-dimensional numerical simulations, we use a dual-grid immersed boundary method for a flow geometry consisting of a single actuated fin in a rectangular domain. The simulated flow field and isotherms indicate the formation of thin thermal boundary layers on the fin and base plate. The tip vortices shed by the fin are instrumental in mixing and transport of temperature field. The active cooling principle described in this work may be employed as an efficient and compact thermal management method for small electronic devices with high power densities.